Testers for combining ability and selection of papaya hybrids resistant to fungal diseases - Vivas,Marcelo (2011)
Genetic resistance represents a sustainable alternative to disease control in papaya crop. The purpose of this study was to evaluate the use of testers to estimate combining ability and select hybrids resistant to black spot, phoma spot and chocolate spot. The experiment was conducted in a randomized block design with two replications and 20 plants per plot. The severity of phoma spot and black spot on leaves and the lesion area of black spot and chocolate spot on fruits were evaluated in two seasons. The combining ability of the following crosses is negative for all traits: tester 'JS 12' with 'Sunrise Solo' and 'Kaphoro Solo PV'; tester 'Americano' with 'Caliman M5', 'Sunrise Solo', 'Baixinho de Santa Amália' and 'Waimanalo'; and tester 'Maradol' with 'Caliman G', 'Caliman AM' and 'Sunrise Solo PT'. These results may be useful in breeding for disease resistance by hybridization.